PELAYANAN KESEHATAN DENGAN METODE PAZ AL KASAW - Sri Kustiyati; Istiqomah Risa Wahyuningsih (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Background: Humans are unique creatures created by Allah in an absolutely prefect form. All organs in the human body are connected by very complex and complete nerves. When there is interference or weakness in one organ, the other organs will signal that weakness. The face and palms are two organs of the body from which weaknesses or disorders that occur in certain organs in the bodu can be identified. Objective: increase partisipans’ knowledge and skills in disease detection through paln analysis. Method: The method of activity is to conduct training, with participants being women in the village of Wonorejo, Polokarto, Sukoharjo. The implementation time is Sunday, July 14 2020. Result: The value of knowledge before the training is 70% less, enough 25% and 5% good. The value of knowledge after training is less 17.5%, 32.5% sufficient and 50% good. The mean score of pre-test knowledge was 4.1 and 7.08 in the post test. Conclusion: The training activity can increase participants’ knowledge and skills in disease detection through palm analysis.